Male description of Eutetrapha velutinofasciata Pic, with a new synonym (Coleoptera: Cerambycidae: Lamiinae: Saperdini) - Lin, Mei Ying; Li, Wenzhu; Yang, Xing Ke (Zootaxa, 2006)
Eutetrapha velutinofasciata Pic was established for a unique female specimen from Beijing, China. Breuning (1952) transferred it to the genus Paraglenea Bates based on one additional female specimen from Inn-shan (China: Inner Mongolia), a transfer which was not widely accepted. We describe the male and postulate the host plant for the first time. Habitus photographs as well as illustrations of the male genitalia and claws are presented. After careful examination of both the holotype of E. velutinofasciata Pic, and the holotype, one paratype, as well as a series of specimens including males and females of Paraglenea nigromaculata Wang et Jiang, P. nigromaculata Wang et Jiang was found to be a junior synonym of E. velutinofasciata Pic.